PROMOTING A SUSTAINABLE LOW-CARBON COMMUNITY THROUGH THE UNIVERSITY'S KNOWLEDGE ENDOWMENT PROJECT FOR MOSQUE - Nur Hanim Ilias; Azran Mansor; Siti Syamimi Omar; Nur Huzeima Mohd Hussain; Atikah Fukaihah Amir, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
Climate change has emerged as a critical global concern, adversely affecting energy consumption and community living environments. Carbon dioxide (CO2) emissions primarily contribute to global warming and climate change, necessitating increased awareness and adoption of low-carbon lifestyles among communities at a micro-scale. While addressing this growing concern, a collaborative effort involving ten university researchers, incorporating faculty members from the built environment department, professional landscape architects, the Masjid As-Siddiq congregation, and related agencies, culminated in the development of the Recycle Edible Garden (REG) as a knowledge endowment project for communities. This paper delves into the methodologies and challenges of knowledge transfer in developing REG as a community low-carbon landscape project. It encompasses low carbon living initiatives, including a recycling and reusing workshop, tree planting with the community, and landscape maintenance sharing sessions with experts. The project was accomplished within a 12-month timeline, yielding favourable results regarding community well-being, mosque landscape enhancement, and heightened awareness regarding carbon mitigation. In summary, the knowledge endowment project, aimed at fostering sustainable low-carbon community awareness, met its objectives within the REG initiative at the community mosque. However, there is a need for continued follow-up and sustainability efforts for the ongoing programs.